Synthesis of Ni-Modified ZSM-5 Zeolites and Their Catalytic Performance in n-Octane Hydroconversion - Wei, Qiang; Zhang, Pengfei; Liu, Xiaodong; Huang, Wenbin; Fan, Xiayun; Yan, Yitong; Zhang, Rongxun; Wang, Lin; Zhou, Yasong (Frontiers in Chemistry, 2020)
The Ni-modified ZSM-5 zeolites with different nickel contents were successfully prepared by the in situ synthesis method and the impregnation method. The synthesized samples were characterized by XRD, SEM, N2 adsorption desorption isothermals and Py-FTIR. The characterization results show that both the textural properties and crystallization of Ni-modified ZSM-5 zeolites were preserved well, and their acidic properties can be modulated after nickel modification. The corresponding NiMo catalysts supported Ni-modified ZSM-5 zeolites were prepared by the incipient wetness co-impregnation method and their catalytic performances were evaluated in n-octane hydroconversion. Compared to the in situ synthesis method, ZSM-5 zeolites modified by the impregnation method exhibit a higher stability and ability with high isomerization selectivity. This is due to the synergistic effect between Brønsted acid sites and Lewis acid sites on the Ni-modified ZSM-5 zeolites.